THE EFFECT OF BRAND AWARENESS, BRAND ASSOCIATIONS, PERCEIVED QUALITY, AND CORPORATE REPUTATION ON THE CUSTOMER SATISFACTION - Susetyo, Ridha Harseno; Ayuni, Risca Fitri (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to examine and explain the influene of  brand awareness, brand association, perceived quality,corporate reputation on customer satisfaction of converse  student  consumers  in  Brawijaya  Universtiy  .  The  research  was conducted in the area of Brawijaya University. Further purposive sampling technique was used in this research with 120 respondents. The analysis tools are Multiple Linear Regression Analysis to determine the relationship between independent variable and dependent variable. The result of the study explained that  there is  a significant  effect  between  brand  awareness,  brand  association, perceived   quality,corporate   reputation   on   customer   satisfaction   partially. Therefore, the research result shows that corporate reputation is the dominant variable that affects customer satisfaction.  Keywords: Brand Awareness, Brand Association, Perceived Quality, Corporate Reputation,Customer Satisfaction